BYPASSING THE HLA SYSTEM IN ORGAN TRANSPLANTATION: OPPORTUNITIES TO ACHIEVE UNIVERSAL COMPATIBILITY VIA FULL SUPPRESSION AND ARTIFICIAL IMMUNOBIOCODING (Journal of Universal Science Research, 2025)
In organ transplantation, the human leukocyte antigen (HLA) system is considered one of the main immunological barriers. HLA molecules are polymorphic antigens that serve as primary alloreactive triggers for the immune response. Incompatibility between donor and recipient HLAs increases the risk of graft rejection. Conventional approaches-such as compatibility matching, desensitization, or long-term immunosuppression-often provide limited efficacy. This study analyzes the potential of partially blocking the HLA system and forming a “Self” signal via artificial biocoding to restrict immune responses in transplantation.